ANALYSIS OF THE SAFETY PERCEPTION IN URBAN TRANSIT WITH THE SUPPORT OF A MULTI CRITERIA METHOD: ANALYSIS OF THE SAFETY PERCEPTION IN URBAN TRANSIT WITH THE SUPPORT OF A MULTI CRITERIA METHOD - Santos, Diego Vieira dos; Chiquieri, Julien; Freitas, Rodrigo Randow de; Gonçalves, Wellington (Brazilian Journal of Production Engineering, 2020)
Traffic safety is one of the most worrying issues in urban planning. In view of the high number of deaths and injuries resulting from traffic accidents, the interventions of the Public Power consist of an attempt to reduce the probability and minimize the risks of traffic accidents and their serious consequences. In order to contribute to the formulation of public policies on the topic, the present work presented the perception of 11 professional drivers in the city of São Mateus (Espírito Santo) about criteria, sub-criteria and alternatives that influence traffic safety, through multicriteria method Analytic Hierarchy Process (AHP). The results suggest that the human attribute is the one that has the highest influence on traffic safety, while education is perceived as the alternative that can directly contribute to improving mobility and safety in this environment. The proposed approach can help policy makers and managers to structure planning and manage actions in relation to global practices and efforts to make the traffic environment safer.
Keywords: Urban mobility; Traffic accidents; Urban planning; Decision making; Strategy.